Europe as a Cultural Project: Turkey and the European Union in the British Press. (19th September 2012) - Phillips, Ryan
<x xml:space="preserve">Abstract</x> An interpretive approach to foreign policy explains the beliefs of actors and the meanings of their actions by locating them in their respective historical traditions and in response to particular dilemmas. This article explains how the British Press constructs 'secularism' as a requirement for Turkey's potential future membership in the European Union (EU) as a response to the rise of the Islamically‐identified Justice and Development Party (AKP). By emphasizing Turkey's secularism as a precondition for entry into the EU, the press effects a significant departure from the dominant British foreign policy traditions with respect to Turkey and the EU, which have highlighted considerations of material benefits. These arguments are pursued through a close analysis of how the British Press covered the attempted election of the country's next president in 2007 and the resulting conflict.